PENDAMPINGAN PENGURUS PONDOK PESANTREN MENGEMBANGKAN WEBSITE SEBAGAI UPAYA MENANGKAL RADIKALISME DI ERA INDUSTRI 4.0 - Wahyudi, Wahyudi; Amrulloh, Hanif; Asnawi, Habib Shulton; Khotamin, Nur Alfi; Yusuf, Muhammad; Santoso, Haris (Al-Khidmat : Jurnal Ilmiah Pengabdian Kepada masyarakat, 2021)
Mobilization in the era of the industrial revolution 4.0 in various joints was extremely fast. This has an impact on the paradigm of people who want to meet their needs instantly, including in the aspect of religious education. Meanwhile, access to information in this era was also used by radicals to carry out propaganda and all things related to it. If these two interests meet (people learn religion instantly and propaganda by radicals) it will certainly endanger the stability and harmony of religious communities in this country. Pesantren as the oldest educational institution in this country must take a role, including building an easy access to information flow, one of which is a website so that the public does not get caught up in radicalist propaganda. Through assistance with the ABCD method, it is hoped that Islamic boarding schools will be able to contribute in spreading friendly Islam in cyberspace. So that radicalism that spreads through the website can be stopped.